2022
DOI: 10.4103/ipj.ipj_126_21
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and quality of life after percuataneous coronary interventions

Abstract: Coronary artery disease (CAD) is the leading cause of morbidity and mortality in the world. However, some fascinating advances in the field of cardiology have not only added years to people's life but life to years as well. Percutaneous coronary intervention (PCI), commonly known as coronary angioplasty is a nonsurgical procedure used to treat stenotic coronary arteries. In recent years, PCI has become the preferred modality of treatment for occluded coronary arteries. However, there has been growing interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…[53] Specifically, 20% to 30% of patients with heart disease were diagnosed with anxiety or depression, and the proportion of patients with anxiety and depression rose to 15% to 43% in the 12 months following an acute heart attack. [54] Our study conducted a meta-analysis of the 3 included studies, and the results showed that empowerment education had a statistically significant effect on the anxiety state of patients after PCI, but had no statistically significant effect on the change of depression state. A recent study on anxiety after PCI found that although patients’ anxiety can be relieved after PCI to a certain extent, smokers, young people and those with low education level are still easy to maintain a high level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[53] Specifically, 20% to 30% of patients with heart disease were diagnosed with anxiety or depression, and the proportion of patients with anxiety and depression rose to 15% to 43% in the 12 months following an acute heart attack. [54] Our study conducted a meta-analysis of the 3 included studies, and the results showed that empowerment education had a statistically significant effect on the anxiety state of patients after PCI, but had no statistically significant effect on the change of depression state. A recent study on anxiety after PCI found that although patients’ anxiety can be relieved after PCI to a certain extent, smokers, young people and those with low education level are still easy to maintain a high level of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…4,36 In this study, informational support, along with support from nurses and next of kin, was associated with reduced fear of complications. This is clinically noteworthy because fear of complications may lead to anxiety, 38,39 which may in turn cause activation of the autonomous nervous system, lowered immune response, impaired heart rate variety, endothelial dysfunction, and vascular inflammation. These symptoms may be associated with worse clinical outcomes following PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Good management, social support, and a holistic approach to health care can help mitigate these impacts (Sannemann et al, 2023). Good health education, emotional support, and appropriate treatment planning can also improve the quality of life for CHD sufferers (Saini et al, 2022). A health care team consisting of doctors, nurses, and other health professionals can provide the support needed to help sufferers manage their condition and improve their quality of life (Lundgren et al, 2022).…”
Section: Introductionmentioning
confidence: 99%